A novel rat monoclonal antibody reactive with murine tumoricidal Kupffer cells and activated peritoneal macrophages from BCG-infected mice. - Someya, A (1986)
A rat monoclonal antibody, termed 1A2.10D and raised against mouse BCG-activated peritoneal-macrophages, was used to detect antigenic determinant(s) on mouse tumoricidal activated peritoneal and liver macrophages from BCG-infected mice by indirect immunofluorescence flow cytometry and immunoblot analysis. This antibody was of the rat IgG2b subclass and not cytolytic to BCG-activated macrophages in the presence of rabbit complement. The antigen(s) was expressed on tumoricidal activated peritoneal and liver macrophages from BCG-infected mice and some macrophage cell lines. Its expression could not be detected on resident peritoneal cells, peritoneal exudate cells containing non- or low tumoricidal macrophages, thymocytes, resting bone marrow cells, normal spleen cells, various established mouse tumour cells or one macrophage cell line. Immunoblot analysis showed the antibody to bind to one major protein of 56,000 MW, and to be expressed on the peritoneal and liver macrophages from BCG-infected mice. Using this antibody and a fluorescence-activated cell sorter, selection was made of antibody-positive or -negative macrophages from BCG-infected mice to examine their tumour killing activity. The antibody-positive macrophages clearly showed higher tumour killing activity than the negative macrophages.